Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2016.08) - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Real-Time Data for Adaptive Management at USAID - Doshi, Samir (Health Communication Innovation Webinar, 2016)

LEARN Monitoring, Evaluation, Research, and Learning Plan - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Program Cycle Road Map - USAID (2016)